Students' Perceptions Toward Practical Online Learning in Physical Education: A Case Study - Cucu Hidayat; Aang Rohyana; Anggi Setia Lengkana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This research aims to evaluate the e-learning system in practical courses in the Physical Education Department based on psychomotor learning outcomes. The research method used is descriptive qualitative, using a survey design with a cross-sectional type for program evaluation. In this case, the program analyzed for evaluation is online-based learning in practical courses based on psychomotor learning outcomes during the Covid 19 pandemic. Questionnaires, interviews, observations, and documentation were used for the data collection. The results explain students' perceptions of the use of online learning media. The interviews results emphasize the following indicators; 1) readiness, 2) facilities and infrastructure, 3) strategies and models, 4) syntax, 5) response, 6) assessment form, 7) success rate, 8) difficulty, 9) overcoming obstacles, 10) weaknesses and strengths, 11 ) Effectiveness. The research proves that online-based practical learning can be implemented. It is proven by students' and lecturers' perceptions regarding the plan, implementation, and evaluation of psychomotor learning. It has been explained comprehensively, especially for the use of media and evaluation of learning used, which is highly highlighted by students and lecturers. Although there are limitations regarding other supporting facilities and infrastructure, it will be a note for further research using different research methods.